Digital Payment on Financial Transactions Towards Economic Growth in South East Asia Emergent Countries - Wibowo, Martino; Mubarok, Faizul; Rahman, Saif-Ur (International Journal of Management and Business Applied, 2025)
Dear Editor-in-Chief, I am pleased to submit my manuscript titled "Digital Payment on Financial Transactions Towards Economic Growth in South East Asia Emergent Countries" for consideration in your esteemed journal. This paper explores the transformative impact of digital payment systems on financial transactions and their subsequent influence on economic growth within emerging economies in Southeast Asia. In this study, I have comprehensively analysed digital payment adoption across various Southeast Asian countries, examining both the benefits and challenges associated with this technological shift. The findings highlight significant correlations between the increased use of digital payments and enhanced economic performance, providing valuable insights for policymakers and financial institutions aiming to foster economic development through technological innovation. I believe this manuscript will be of great interest to your readers, as it addresses a timely and relevant topic with implications for both academic research and practical applications in the financial sector. The paper contributes to the existing literature by offering a nuanced understanding of how digital payment systems can drive economic growth in emerging markets, a subject that is increasingly pertinent in today's rapidly evolving financial landscape. I confirm that this manuscript has not been published elsewhere and is not being considered by any other journal. All authors have approved the manuscript and agree with its submission to the International Journal of Management and Business Applied. We have no conflicts of interest to disclose. Thank you for considering my submission. I look forward to your positive response. Best Regards, Martino Wibowo